2018
DOI: 10.1002/brb3.903
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative disease biomarkers Aβ1–40, Aβ1–42, tau, and p‐tau181 in the vervet monkey cerebrospinal fluid: Relation to normal aging, genetic influences, and cerebral amyloid angiopathy

Abstract: BackgroundThe Caribbean vervet monkey (Chlorocebus aethiops sabaeus) is a potentially valuable animal model of neurodegenerative disease. However, the trajectory of aging in vervets and its relationship to human disease is incompletely understood.MethodsTo characterize biomarkers associated with neurodegeneration, we measured cerebrospinal fluid (CSF) concentrations of Aβ1–40, Aβ1–42, total tau, and p‐tau181 in 329 members of a multigenerational pedigree. Linkage and genome‐wide association were used to elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 61 publications
4
20
0
Order By: Relevance
“…CSF insulin levels were undetectable. Given that decreased CSF Aβ is indicative of increased plaque formation within the brain (Tapiola et al, 2009), these data indicate that T2D monkeys display biomarkers of early amyloid deposition and pre-symptomatic AD (Kalinin et al, 2013; Chen et al, 2018; Latimer et al, 2019) triggered by a state of energy dysregulation, which is consistent with previous work in rodent models (Macauley et al, 2015; Stanley et al, 2016).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…CSF insulin levels were undetectable. Given that decreased CSF Aβ is indicative of increased plaque formation within the brain (Tapiola et al, 2009), these data indicate that T2D monkeys display biomarkers of early amyloid deposition and pre-symptomatic AD (Kalinin et al, 2013; Chen et al, 2018; Latimer et al, 2019) triggered by a state of energy dysregulation, which is consistent with previous work in rodent models (Macauley et al, 2015; Stanley et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…Monkeys were older, ranging from 16 to 23 years (Table 1), which represents the last 30% of lifespan for this species and is a typical age range for the onset of metabolic diseases and neuropathological changes associated with AD (Kalinin et al, 2013; Chen et al, 2018; Latimer et al, 2019). There were no differences in body weight or waist circumference between groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their evolutionarily close relationship to humans, NHPs are essential for the study of age-associated changes in the brain and other central nerve system diseases ( Chu et al, 2014 ; Feng et al, 2019 ; Qin et al, 2013 ; Zhang et al, 2014 ). Studies have indicated that CSF levels of Aβ 40 and Aβ 42 decrease significantly with age in cynomolgus and vervet monkeys ( Chen et al, 2018 ; Yue et al, 2014 ). However, no study has investigated the relationship of FA concentrations in CSF samples from different aged rhesus monkeys or the correlation between FA and Aβ levels in CSF samples.…”
Section: Dear Editormentioning
confidence: 99%
“…The vervet monkey (genus Chlorocebus) is an Old World monkey frequently used as a model in biomedical research (Jasinska et al 2013;Jasinska 2019) particularly for complex chronic diseases, many of which either are associated with aging or aggravate the process of aging. Vervets exhibit some aspects of human aging, including neurodegeneration (Postupna et al 2017;Kalinin et al 2013;Chen et al 2018;Latimer et al 2019), reproductive senescence and menopause (Atkins et al 2014). Vervets have also been used in studies of reproductive physiology and obesity (Kuokkanen et al 2016), the effects of genes and diet on growth and obesity (Schmitt et al 2018), cardiometabolic health (Voruganti et al 2013), physiological and behavioral stress responses Jasinska, Pandrea, et al 2020), and multi-tissue genetic regulation of gene expression, including that in tissues involved in stress responses (Jasinska et al 2017).…”
Section: Introductionmentioning
confidence: 99%